PENINGKATAN STATUS BESI DAN KEBUGARAN FISIK PEKERJA WANITA USIA SUBUR - Yaktiworo Indriani; Ali Khomsan; Dadang Sukandar; Hadi Riyadi; Reni Zuraida (Jurnal Gizi dan Pangan, 2011)
The study aims were to (1) assess the nutritional status, adequacy level, and physical fitness of the nonpregnant reproductive female workers, and (2) analyze the effect of micronutrients supplementation on their iron status and physical fitness. This research employed experimental design of double blind, completely randomized design by involving 338 households of female workers. The experimental unit consists of 39 female workers whose hemoglobin level were 80-125 g/L. However, five of them were drop out due to pregnancy or sickness. The treatments applied in the study were three capsules containing: (1) iron and folic acid (BF), (2) multi-vitamin and mineral (MVM), which contains of 15 different vitamins and minerals, and (3) placebo (P). The body mass index of the female workers were thin 12 percent, normal 70 percent and overweight 18 percent. Most of their nutritional intake of vitamin C, calcium and iron were deficient but they had a good to superior of physical fitness. After 10 weeks of three days per week supplementation, BF significantly increased the hemoglobin (p